Progressively Disrupted Somatodendritic Morphology in Dopamine Neurons in a Mouse Parkinson’s Model - Lynch, William B. (Mov Disord, 2018)
BACKGROUND: Parkinson’s disease is characterized by the progressive loss of dopamine neurons in the substantia nigra, leading to severe motor deficits. Although the disease likely begins to develop years before observable motor symptoms, the specific morphological and functional alterations involved are poorly understood. OBJECTIVES: MitoPark mice lack the gene coding for mitochondrial transcription factor A specifically in dopamine neurons, which over time produces a progressive decline of neuronal function and related behavior that phenotypically mirrors human parkinsonism. Our previous work identified a progressive decrease in cell capacitance in dopamine neurons from MitoPark mice, possibly suggesting reduced membrane surface area. We therefore sought to identify and quantify somatodendritic parameters in this model across age. METHODS: We used whole-cell patch clamp and fluorescent labeling to quantify somatodendritic morphology of single, neurobiotin-fllled dopamine neurons in acutely isolated brain slices from MitoPark mice. RESULTS: We found that MitoPark mice exhibit an adultonset, age-dependent reduction of neuritic branching and soma size in dopamine neurons. This decline proceeds similarly in MitoPark mice of both sexes, but does not begin until after the age that early decrements in ion channel physiology and behavior have previously been observed. CONCLUSIONS: A progressive and severe decline in somatodendritic morphology occurs prior to cell death, but is not responsible for the subtle decrements observable in the earliest stages of neurodegeneration. This work could help identify the ideal time window for specific treatments to halt disease progression and avert debilitating motor deficits in Parkinson’s patients.